Etika Kepada Tuhan, Manusia, dan Lingkungan Perspektif Filsafat Etika Islam: Ethics towards God, Humans and the Environment Perspective of Islamic Ethics Philosophy - Almutawallid, Almutawallid; Sopu, Salahuddin; Santalia, Indo (Undiksha, 2024)
This research examines ethics towards God, humans and the environment from the perspective of Islamic ethics, using an Islamic philosophy approach. The method used in this research is descriptive analysis. The descriptive analysis method is used with the aim of explaining the nature of ethics as humans towards God and others. humans, and the environment, as well as explaining the relevance of these three elements which are inseparable from each other using the perfective Islamic Philosophy of Ethics. This type of research is library research, namely collecting several pieces of literature such as books, e-books, journals, research that discusses the theme being discussed. The results of this research reveal that ethics towards God is rooted in recognition and submission as a form of moral obligation as a servant through worshiping Him and giving thanks for all His gifts. Second, ethics towards humans is understood as a form of awareness of their nature as social creatures by maintaining and achieving a balance between personal rights and social obligations, then ethics towards the environment is understood as a form of moral awareness that humans and society are part of the universe itself so that protecting it is a form of safeguarding interests. Humans themselves, like the ecosystem of the universe, need each other, the interconnection of these three aspects involves the fulfillment of responsibility for their duties as social creatures and caliphs on earth. This moral awareness arises because of the human ability to differentiate between good and bad, halal and haram, a conscious human being is one who truly understands that he is responsible for his actions. Relations between humans and the environment are represented by protecting and managing nature well, maintaining relationships with the environment and humans as a form of ethics towards God, because in kalam science, the universe and humans are manifestations of God himself and humans' relationship to God can be assessed. from relationships with each other and the surrounding environment, acting and behaving as if receiving guidance from God.